KECEMASAN SISWA KETIKA DATANG TERLAMBAT KE SEKOLAH (Suatu Narrative Inquiry Pada Siswa SD Negeri Pasirbuah) - Anita, Anita; Suratno, Tatang; Fatihaturosyidah, Fatihaturosyidah (Didaktika, 2022)
Late come to school is things that are not foreign again in the world of education. Good researcher nor reader, of course once experience or watching late come to school. Late come to school is one attitude disciplinary because violate regulations. Not could denied that when we do violation to something rules, anxiety could felt and shown through motion body or expression face. Motivation is moving thing somebody in do something deed. Including discipline someone can too influenced by motivation. On research this, researcher looking for data about reason students and the anxiety that occurs in students when come late to school. Subject study this that is Pasirbuah State Elementary School students who are late come to school. Narrative inquiry chosen as method research this time. Observation field, interviews, story telling , field notes, and studies document used in find the data needed related retrieved title. With tell return experience participant when come late to school, strengthened with theories from experts, interviews students and parents, can be taken conclusion that reason most student when come late to school that is Wake up oversleep. And the anxiety that occurs no many showed when at school. However anxiety that occurs in students who are late show it at home with attitude restless and easy angry to parents her.